2012
DOI: 10.1016/j.comptc.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional study of LixMoS2 intercalates (0⩽x⩽1)

Abstract: RECEIVED DATEThe stability of Lithium intercalated 2H-and 1T allotropes of Molybdenum disulfide (Li x MoS 2 ) is studied within a density-functional theory framework as function of the Li content (x) and the intercalation sites. Octahedral coordination of Li interstitials in the van der Waals gap is found as the most favorite for both allotropes. The critical content of Lithium, required for the initialization of a 2H 1T phase transition is estimated to x 0.4. For smaller Li contents the hexagonal 2H crystal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
107
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 57 publications
12
107
1
4
Order By: Relevance
“…The obtained lattice parameters for all polytypes are in good agreement with experimental and theoretical values reported earlier [11,25,30]. Consistent with experimental observations, we found that 2H is energetically the most favorable polytype of MoS 2 (see Table S1 in SD) [24].…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained lattice parameters for all polytypes are in good agreement with experimental and theoretical values reported earlier [11,25,30]. Consistent with experimental observations, we found that 2H is energetically the most favorable polytype of MoS 2 (see Table S1 in SD) [24].…”
Section: Methodssupporting
confidence: 92%
“…In its natural state, MoS 2 is generally found in its most stable form with a hexagonal 2H crystal structure [11], while a high energy tetragonal 1T polytype can also be stabilized via liquid-state exfoliation [22]. Moreover, several experimental and theoretical studies have pointed out a coexistence of 2H crystal symmetry with a closely related rhombohedral 3R symmetry [23,24], while a few studies have also investigated a hypothetical tetragonal 2T structure [25]. Using first principles density functional theory calculations, here we analyze the structural stability, electronic structure, and intercalation voltages for Na intercalation compounds with 2H, 3R, as well as 1T and 2T polytypes of MoS 2 .…”
Section: Introductionmentioning
confidence: 97%
“…The optimized lattice constant of unit cell is a = 3.166 Å, which is in agreement with previous report [30]. Four representative adsorption sites of Li are considered in our calculations: (1) the top site of a S atom in upper plane; (2) the top site of a S atom in lower plane; (3) the top site of a Mo atom; and (4) the bridge site above a S-Mo bond.…”
Section: Resultsmentioning
confidence: 83%
“…The results can be considered good compared with the available result. [13] Interestingly, upon hybridization, the expected increase in the system energy is only as small 0.03 eV, which is only 10% of the energy difference between the 1T and 2H phases (0.28 eV). This indicates that the stability of the hybridized system should be much higher than that of the pure 1T phase, being even closer to that of the 2H phase.…”
mentioning
confidence: 99%